Pemberdayaan UMKM Desa Tambakan melalui Olahan Nugget Udang Keju dan Pemasaran Digital: Pengabdian - Izah, Nikmatul; Sholiha, Illiyatus; Alfand, Mochammad Fitrah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve the technical skills and digital literacy of PKK women in Tambakan Village, Bangil District, Pasuruan Regency, through training in processing cheese shrimp nuggets and digital marketing socialization. The program was held on July 18, 2025 by involving 38 participants using a community-based participatory approach. The training includes shrimp cleaning, ingredient mixing, dough formation, and frying, while marketing socialization includes the use of Instagram, Shopee, and Canva. The results of the activity showed that 89.5% of participants understood the production process, 81.6% were interested in starting a home business, and 76.3% were interested in marketing products online. This program has succeeded in improving production and marketing skills while opening up opportunities for the development of a maritime economy based on local potential. This activity proves that the collaboration of training on processed pond products and digital literacy can be an effective strategy in empowering village MSMEs in a sustainable manner.